25 years of the Brasilia Peace Agreements - Maúrtua de Romaña, Óscar (2023)
In commemoration of the celebration of the fifth quinquennium since the Brasilia Peace Accords between Peru and Ecuador, this article delves into the enduring diplomatic relationship between both nations, from historical conflicts to milestones of collaboration. The Agreements signed in 1998 marked the beginning of an era of economic collaboration that was reflected in the growth of bilateral trade and significant foreign direct investment. In addition, the fruitful Peruvian-Ecuadorian relationship covers areas such as sustainable development, education, health care and energy. Also, the Agreements played a fundamental role in strengthening regional security, stopping the production of illicit drugs and improving the position of nations in international forums. In essence, the Brasilia Peace Accords serve as a legal and diplomatic model for conflict resolution, fostering lasting peace and prosperity.